Dawr al-mu'asasah al-Islamiyah bi-Kelantan fi nashar al-tarbiah al-Islamiah fi Wilayah Kelantan - Asiah Bt Muhammad Nor (Universiti Sains Islam Malaysia, 2014)
The Academic Project Paper was discussed about the role of Kelantan Islamic Foundation in develop the Islamic education for this state. The researcher had used two methods to find and get the information which related to that foundation through the library research and interview. The purpose of this research is to study with detail about the funtions of "Yayasan Islam Kelantan" in spread widely the Islamic education especially for all religious school in Kelantan, Modern Pondok in Bachok and Arabic Language Centre at Nilam Puri.The research also, mention about the evaluation of education according to Islamic perspective and Kelantan Islamic Foundation.